The importance of terms of trade in the Colombian economy - Andrés Felipe Oviedo Gómez; Lya Paola Sierra Suárez (CEPAL Review, 2019)
Commodities represent the lion's share of Colombia's exports, and the terms of trade are directly determined by the prices of these commodities, making a detailed analysis of this variable's impacts on the country's economy essential. This paper examines the effects of terms-of-trade shocks on output, investment, consumption, the trade balance, the real exchange rate and inflation in Colombia. An extensive database comprising 129 variables of economic activity in 2001–2016 was used, along with a FAVAR model. The results suggest that terms-of-trade shocks have significant impacts on the Colombian economy, as they explain roughly 5% of the variation in the country's economic activity, 8% in investment, 6% in the trade balance and 1% in the real exchange rate.